Pengaruh Konten Kreatif, Influencer, Dan Kepercayaan Digital, Terhadap Minat Beli Konsumen Generasi Z Pada Live Thrift - Rulistia Arga Ardana; Harun Alrasyid; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract Digital transformation has reshaped how consumers obtain information, interact with sellers, and make purchasing decisions through social media. TikTok has emerged as a prominent platform by integrating live streaming features for marketing and transactional activities, including the rise of live thrift shopping. This study aims to analyze the influence of creative content, influencers, and digital trust on Generation Z's purchase intention in TikTok live thrift activities. A quantitative approach was employed using a survey method involving 100 respondents who met the criteria as TikTok users from Generation Z. Data were analyzed through multiple linear regression using SPSS version 26. The findings reveal that creative content, influencers, and digital trust have positive and significant effects on purchase intention, both partially and simultaneously. These results suggest that live-stream-based marketing strategies should emphasize engaging content presentation, credible communicators, and trust-building mechanisms to enhance promotional effectiveness and stimulate consumer purchasing decisions Keywords: Purchase Intention, Creative Content, Influencers, Digital Trust, Generation Z, TikTok Live Thrift